The Influence of Service Quality, InformationQuality, and System Quality on Perceived Value on Customer Satisfaction - Olivia Inger Pitaloka; Rhian Indradewa (Publikasi Indonesia, 2025)
This study aims to evaluate the influence of Service Quality, Information Quality, and System Quality on Customer Satisfaction mediated by Perceived Value in the context of e-learning usage among students in Java. The research background highlights the importance of enhancing student satisfaction with e-learning to support the effectiveness of online learning processes. This research employed a quantitative approach using Structural Equation Modeling –Partial Least Squares (SEM-PLS). The research sample comprised 137 active students utilizing e-learning platforms from universities in Java. The results indicated that Service Quality, Information Quality, and System Quality significantly influenced Perceived Value. Service Quality and System Quality had a significant effect on Customer Satisfaction, whereas Information Quality did not directly impact Customer Satisfaction significantly. The study recommends that universities improve system and service quality and enhance information quality in e-learning platforms to increase Perceived Value and student satisfaction. This research contributes deeper insights for university management to effectively manage e-learning platforms and enhance student satisfaction